Currículo vs narrativas ordinárias - Daros, Lucas Daniel (2013)
The present dissertation presents the results obtained through a research carried out with 24 students and 2 teachers of the second year of high school in a public Curitiba. The research aims to recognize the practices of reading the ordinary subjects, in this case students, based on their assessments about the act of reading. Once identified, the assessments are with the interests proposed by the prescriptive documents on the teaching of reading. The research, conducted through interviews, identifies preferences and personal tastes; criteria for choosing readings; experiences in reading; and perceptions about reading in and out of high school. In this sense, the place and the reading space within the college are confronted by the agents of education. The analysis of documents and interviews is done according to concepts proposed by the theories of Michel de Certeau and the Aesthetics of Reception proposed by Wolfgang Iser. At the end of the research, a of reading among students, teachers and prescriptive documents. Such crisis of representativeness groups questions about the legitimacy of the readings and the objectives of teaching reading within the college, which identifies apparently distinct interests between students and the Institution.